Portrait of Islamic Religious Education of the Indonesian Migrant Community in Taiwan: (Study of the Expression of Islamic Religious Education of Indonesian Migrants in Taiwan) - Muttaqin, A. Nanan Najmul; Rohmah, Liatul; Akhyak, Akhyak; Fitri, Agus Zainul (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2024)
The aim of this research is to provide an overview of the Islamic Religious Education of the Indonesian migrant community in Taiwan, its learning methods and its impact on the Indonesian migrant community in Taiwan. The approach used in this study is a qualitative approach. This type of research is field research. This research design uses a case study of the expression of Islamic Religious Education. The data collection strategy is carried out in natural settings, primary data sources, and data collection techniques include participant observation, in-depth interviews and documentation. As a result, community groups, mosques, information technology, and social media have played a significant role in providing Islamic educational resources. Islamic education methods are grouped into three; covers aspects of teaching, learning, and organizing Islamic activities. Islamic religious education has a positive impact on the social life of the Indonesian migrant community in Taiwan, increasing religious identity, social integration, and fostering attitudes of tolerance.